The pattern of land use integration in historic areas in the CBD zone: Comparative study of space syntax attributes of Malang, Melaka, and Kanazawa - Bonifacius, Nurhamdoko; Mohamad, Effendi; Tutuko, Pindo; Yuniawan, Dani; Aini, Nurul; Zhenjiang, Shen; Yamato, Yuya; Sulaksono, Aditya Galih (SPSD Press, 2022)
The issue of sustainability is an interesting discussion on every concept of development in all cities worldwide. One issue in urban development concerns urban sustainability. It is widely understood in urban development that the distribution of land use directly impacts the sustainability of cities. The history of the city always impacts the distribution of land use. This study examines the relationship between land use distribution and the spatial structure of the road network and their contribution to urban sustainability in Central Business District (CBD) zone-based areas having historical value. Cities planned during ancient times are used as research objects. Connectivity and depth are used as syntax space attributes. Malang, Melaka and Kanazawa cities are chosen for this study for their historical value. Comparative studies were carried out by calculating the connectivity and integration axial lines of three cities in the CBD zone. DepthMapX is a space syntax tool for calculating the space syntax attributes used for this study. The study results are expected to help determine the integration concerning specific city zones. Furthermore, it will be able to gauge the suitability of the distribution pattern of land use and the spatial configuration pattern for these historic cities.